Identification of trichodinids (Ciliophora: Trichodinidae) from red tilapia (Oreochromis niloticus x O. mossambicus) in Pathumthani Province, Thailand - Worakrit Worananthakij (Faculty of Veterinary Medicine, 2020)
Chiang Mai Veterinary Journal” (ISSN-print as 1685-9502 and ISSN-online as 2465-4604) before officially changing over to an electronic platform. The newly formatted journal is entitled “Veterinary Integrative Sciences” (ISSN as 2629-9968).